Ammonium Transporter 1 (AMT1) Gene Family in Pomegranate: Genome-Wide Analysis and Expression Profiles in Response to Salt Stress - Fatima Omari Alzahrani (Current Issues in Molecular Biology)
Understanding the ammonium (NH4+) uptake and transport systems, particularly AMT1 genes, is important for plant growth and defense. However, there is a lack of research on identifying and analyzing AMT1 genes in pomegranate, emphasizing the need for further investigation in this area. Five AMT1 genes (PgAMT1-1 to PgAMT1-5) were identified, all of which contain the PF00909 domain, a feature of ammonium transporters. Various characteristics of these genes, including gene length, coding sequence length, and chromosomal locations, were examined. This study evaluated the isoelectric point, hydropathicity, conserved domains, motifs, and synteny of the PgAMT1 proteins. Phylogenetic analysis confirmed the homology of PgAMT1 genes with previously reported AMT in Arabidopsis and tomato. The tissue-specific expression analysis of PgAMT1 genes revealed distinct patterns: PgAMT1-1 and PgAMT1-2 were predominantly expressed in flowers, PgAMT1-3 exhibited notable expression in roots, leaves, and flowers, PgAMT1-4 was primarily expressed in leaf tissue, while the expression of PgAMT1-5 was detected in both leaves and roots. The impact of salt-induced stress on AMT1 gene expression was also examined, revealing that PgAMT1-1, PgAMT1-2, and PgAMT1-4 expression is reduced under increased salt stress. These expression modifications can help regulate NH4+ assimilation in conditions of elevated salinity, maintaining cellular homeostasis and ion balance. This study contributes to the comprehensive identification of the AMT1s gene family in pomegranate; however, further research on the functional characterization of the identified PgAMT1s is needed.